2021
DOI: 10.3390/ani11030792
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Mitigation of African Swine Fever Virus in Feed

Abstract: Since the 2013 introduction of porcine epidemic diarrhea virus into the United States (U.S.), feed and feed ingredients have been recognized as potential routes for the introduction and transmission of foreign animal diseases of swine. Feed ingredients for swine diets are commodities traded worldwide, and the U.S. imports thousands of metric tons of feed ingredients each year from countries with circulating foreign animal diseases. African swine fever (ASF) is the most significant foreign animal disease threat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 96 publications
3
46
0
Order By: Relevance
“…A recent study developed a new mathematical model to reconstruct the between-farm PRRSV dynamics, revealed the role of between-farm pig movements, indirect contacts by farm-to-farm proximity, and the continued circulation of PRRSV within infected sites (re-break) (Galvis et al, 2021). Despite the promising results, the study did not fully consider indirect contacts formed by the between-farm transportation vehicles networks, which has been previously described as one the major modes of the between-farm transmission of disease in swine (Büttner and Krieter, 2020; Porphyre et al, 2020; Niederwerder, 2021), and also in other systems such as cattle (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…A recent study developed a new mathematical model to reconstruct the between-farm PRRSV dynamics, revealed the role of between-farm pig movements, indirect contacts by farm-to-farm proximity, and the continued circulation of PRRSV within infected sites (re-break) (Galvis et al, 2021). Despite the promising results, the study did not fully consider indirect contacts formed by the between-farm transportation vehicles networks, which has been previously described as one the major modes of the between-farm transmission of disease in swine (Büttner and Krieter, 2020; Porphyre et al, 2020; Niederwerder, 2021), and also in other systems such as cattle (Yang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Contaminated feed ingredients have been recognized as possible routes for between-farm pathogen transmission (Niederwerder, 2021), however the probabilities of PRRSV transmission through them have been described as relatively low (Cochrane et al, 2017; Ochoa et al, 2018). Dee et al 2020, experimental study demonstrated that pigs that consumed pellet feed contaminated with 1×10 5 TCID50/ml of PRRSV exibeted clinical signs (Dee et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple routes of ASFV transmission to domestic swine have been characterized including domestic swine to domestic swine, wild suids to domestic swine, and via the soft tick of the Ornithodoros genus serving as a vector [ 6 ]. Within these, multiple mechanisms of transmission can occur whereby domesticated swine become infected with ASFV including direct animal contact, contact with contaminated fomites, or exposure to contaminated feedstuffs or water [ 7 ]. Extended stability of ASFV within pork products has been widely documented [ 8 ], detection of ASFV DNA within pork products crossing international borders has been documented [ 9 , 10 ], and strong evidence of ASFV transmission via contaminated food products has been documented [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%